Entrepreneurship Development Perspectives in the Republic of Moldova. Case Study – Central Region - Ina Mogildea; Ludmila Mogildea; Maria Magdalena Turek Rahoveanu (Journal of Agriculture and Rural Development Studies)
The development of entrepreneurship in the central area of the Republic of Moldova is particularly important for the economic growth of the region and the country, for creating jobs, stimulating innovation and reducing the gaps between urban and rural areas, with an impact on improving the quality of life of the area's inhabitants. The development of entrepreneurship can play an essential role in reducing economic disparities between urban and rural areas, by creating jobs, diversifying the economy, improving infrastructure and access to resources, and contributing to the balanced economic development of the region. Thus, the Central Region has the potential to become an economic engine that positively influences the entire nation, contributing to social and economic stability and the integration of the Republic of Moldova into the global economy. The purpose of this paper is to present the results of an investigation at the level of the Central Region of the Republic of Moldova that took into account the perspectives of balanced economic development of the region based on the competitive advantages it offers to potential entrepreneur.